1961
DOI: 10.1002/jlac.19616420102
|View full text |Cite
|
Sign up to set email alerts
|

Umlagerungen organischer Anionen, I. Stereochemischer Ablauf der Umlagerung des metallierten Benzyl‐sek.‐butyl‐äthers; ein Beitrag zum Problem der SNi‐Substitution

Abstract: Die Isomerisation des optisch aktiven Lithium-benzyl-sek.-butyl-iithers in nicht-protonenaktiven Solvenzien zum Lithiumsalz des Phenyl-sek.-butylcarbinols vollzieht sich unter weitgehender Racemisierung der sek.-Butyl-Gruppe. Die restfiche AktivitZt bleibt im Sinne einer Retention der Konfiguration erhalten. Das AusmaO der Racemisierung (87-67%) nimmt zu mit wachsender Fahigkeit des Solvens zur Solvatation von Kationen und mit steigender Temperatur. -Als Mechanismus der Umlagerung wird eine zu Benzaldehyd und … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1964
1964
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…A dissociation-recombination (ion-pair) mechanism was proposed as illustrated below for benzyl sec-butyl ether (III). Schollkopf and coworkers further suggested that this might be a common mechanism for the Wittig, Stevens, and Meisenheimer rearrangements (18).…”
Section: Rebirthmentioning
confidence: 98%
“…A dissociation-recombination (ion-pair) mechanism was proposed as illustrated below for benzyl sec-butyl ether (III). Schollkopf and coworkers further suggested that this might be a common mechanism for the Wittig, Stevens, and Meisenheimer rearrangements (18).…”
Section: Rebirthmentioning
confidence: 98%
“…Termination at both positions is allowed in each instance, and inductive effects are held responsible for the observed selectivity. Specifically, the methyl group is held to supply electron density to the ring carbon by an inductive and hyperconjugative interaction mechanism (18). Studies with the 2,3,7,7-tetramethyl compound indicate that the methyl substituent at carbon atom 3 exhibits a stronger directive influence than that at carbon atom 2 in the methyl migration reaction (19).…”
Section: Secondary Steric Effectsmentioning
confidence: 99%
“…This has the effect of stabilizing the ir-ir* transition. Thus, a dramatic rate enhancement is observed in the internal electrocyclization of 2,3-homotropone, which is believed to occur via a t-tt* transition (18). Similarly, the (6 + 6) 7r-type photocyclization of tropone was first observed only when 2N H2S04 was used as the solvent (35).…”
Section: Solvent Effectsmentioning
confidence: 99%
“…3-Bromo-3-methyl-l-butyne gave a very high yield of 3-methyl-1,2-butadiene with lithium aluminum hydride, but the pure starting bromide was not obtained in good yield. 4 Possibly triphenyl phosphite dibromide14 would yield such tertiary propargyl bromides in good yield. Both zinc-copper couple (12) M. Bouis, Bull.…”
Section: Lía1d4mentioning
confidence: 99%